Slovenia : Consolidated Risk Based Supervision - Gutierrez Garcia, Joaquin (World Bank, Washington, DC, 2013)
This Technical Note, of an informal nature, summarizes our recommendations based on the current scope of discussions with supervisors of BoS in charge of supervising the Target Group, including several meetings organized by the latter with management of the parent bank. The Note is organized in three sections. The first section includes a summary of our main recommendations. The second section presents a few strategic issues we noted, which may be of interest to BoS going forward as it implements risk based supervision. The third and last section proposes a series of elements to continue the supervision of the Target Group going forward, including how to assess internal governance in a practical manner. Given the depth of issues involved, and that in internal governance the importance is in the details, on purpose this Technical Note is long in providing detailed recommendations on how to implement consolidated risk based supervision.